Critical Knowledge Gap in Blood Transfusion Among University Students in Iraq : Kesenjangan Pengetahuan Kritis dalam Transfusi Darah di Kalangan Mahasiswa di Irak - Mohammad, Noor J. (Academia Open, 2024)
Background: Blood transfusion, a crucial part of modern medical treatment, is believed to be the first successful organ transplant and plays a vital role in modern healthcare interventions. Knowledge gap: Despite its importance, awareness and knowledge about blood transfusion and donation are insufficient, particularly among university students. Aims: This study aims to assess student knowledge regarding blood transfusion and to raise awareness about blood donation. Methods: A cross-sectional study at Bab Al-Zubair University involved 200 students, assessing blood transfusion knowledge using a questionnaire and SPSS version 16, with statistical analysis. Results: The study revealed that 46% of students had no knowledge of blood transfusion, while only 31% had information on transfusion and donation. Social media was the primary information source for 32% of students, with only 9% undergoing regular blood tests. Moreover, 82.5% of students had never attended a seminar on blood donation. Novelty: This study highlights a significant gap in knowledge and awareness among students regarding blood transfusion and donation, emphasizing the role of social media as a key information source. Implications: The study emphasizes the need for targeted educational interventions in university curricula to enhance student awareness and knowledge about blood donation and transfusion. Highlights: Knowledge Gap: 46% of students lack information on blood transfusion. Seminar Absence: 82.5% never attended blood donation seminars. Educational Need: More training and seminars required to increase awareness. Keywords: Blood transfusion, Student knowledge, Blood donation, Awareness, Cross-sectional study